Developing military environmental literacy in the South African Army through a dedicated military environmental management course - Smit, HAP (Scientia Militaria - South African Journal of Military Studies, 2020)
It is important for soldiers to be military environmentally literate to prevent unacceptable behaviour in the environment in which they conduct their missions. This is especially true during peacekeeping and disaster relief mission, but holds equally true for combat situations. Military environmental literacy is the nature and level of the attitude toward, knowledge about, and behaviour in and toward the environment in which the military operates. The construct of military environmental literacy (MEL) consists of three components, military environmental attitude (a general feeling of favour or disfavour toward the military environment, i.e. the environment in which the military operates), military environmental knowledge (the ability to identify a number of concepts and behaviour patterns related to the military environment, i.e. the environment in which the military operates), and military environmental behaviour (a demonstration of how one acts toward or in the military environment in which the military operates). The MEL of South African Army soldiers were measured in a study reported on in 2017, as well as in a test-retest survey in 2018. A specially developed valid and reliable questionnaire to test military environmental literacy was used in both surveys. This article argues that exposing soldiers to a dedicated military environmental management course can positively influence their military environmental literacy.